Efficacy of 12 weeks oral beta‐alanine supplementation in patients with chronic obstructive pulmonary disease: a double‐blind, randomized, placebo‐controlled trial. Issue 5 (17th August 2022) - De Brandt, Jana; Derave, Wim; Vandenabeele, Frank; Pomiès, Pascal; Blancquaert, Laura; Keytsman, Charly; Barusso‐Grüninger, Marina S.; de Lima, Fabiano F.; Hayot, Maurice; Spruit, Martijn A.; Burtin, Chris
Abstract: Background: Beta‐alanine (BA) supplementation increases muscle carnosine, an abundant endogenous antioxidant and pH buffer in skeletal muscle. Carnosine loading promotes exercise capacity in healthy older adults. As patients with chronic obstructive pulmonary disease (COPD) suffer from elevated exercise‐induced muscle oxidative/carbonyl stress and acidosis, and from reduced muscle carnosine stores, it was investigated whether BA supplementation augments muscle carnosine and induces beneficial changes in exercise capacity, quadriceps function, and muscle oxidative/carbonyl stress in patients with COPD. Methods: In this double‐blind, randomized, placebo (PL)‐controlled trial (clinicaltrials.gov identifier: NCT02770417), 40 patients (75% male) with COPD (mean ± standard deviation: age 65 ± 6 years; FEV1 % predicted 55 ± 14%) were assigned to 12 weeks oral BA or PL supplementation (3.2 g/day). The primary outcome, i.e. muscle carnosine, was quantified from m. vastus lateralis biopsies obtained before and after intervention. Co‐primary outcomes, i.e. incremental and constant work rate cycle capacity, were also assessed. Linear mixed model analyses were performed. Compliance with and side effects of supplement intake and secondary outcomes (quadriceps strength and endurance, and muscle oxidative/carbonyl stress) were also assessed. Results: Beta‐alanine supplementation increased muscle carnosine in comparison with PL in patients with COPD (mean difference [95% confidence interval]; +2.82 [1.49–4.14] mmol/kg wet weight; P < 0.001). Maximal incremental cycling capacity (VO2 peak: +0.5 [−0.7 to 1.7] mL/kg/min; P = 0.384, Wpeak: +5 [−1 to 11] W; P = 0.103) and time to exhaustion on the constant work rate cycle test (+28 [−179 to 236] s; P = 0.782) did not change significantly. Compliance with supplement intake was similar in BA (median (quartile 1–quartile 3); 100 (98–100)%) and PL (98 (96–100)%) ( P = 0.294) groups, and patients did not report side effects possibly related to supplement intake. No change was observed in secondary outcomes. Conclusions: Beta‐alanine supplementation is efficacious in augmenting muscle carnosine (+54% from mean baseline value) without side effects in patients with COPD in comparison with PL. However, accompanied beneficial changes in exercise capacity, quadriceps function, and muscle oxidative/carbonyl stress were not observed.